CGF Membrane Promotes Periodontal Tissue Regeneration Mediated by hUCMSCs through Upregulating TAZ and Osteogenic Differentiation Genes. (5th August 2021) - Li, Wenjing; Wang, Feifei; Dong, Fusheng; Zhang, Zhiyong; Song, Peng; Chen, Huizhen; Wang, Jie
Abstract : Concentrated growth factor (CGF) membranes are widely used in basic and clinical research of soft and hard tissue regeneration, but its effect on periodontal tissue regeneration is less studied. This study explored the role of CGF membranes in periodontal tissue regeneration mediated by human umbilical cord mesenchymal stem cells (hUCMSCs). HUCMSCs and human periodontal ligament fibroblasts (HPLFs) were extracted and identified by microscope and flow cytometry. The effects of the extracted CGF membrane on cell viability, osteogenic differentiation ability, osteopontin (OPN) expression, alkaline phosphatase (ALP) content, and osteogenic differentiation-related genes (Runt-related transcription factor 2 (RUNX2); osteocalcin (OCN); ALP), Tafazzin (TAZ) expression, and nuclear transfer were examined by MTT assay, alizarin red staining, immunofluorescence, enzyme-linked immunosorbent assay (ELISA), quantitative real-time polymerase chain reaction (qRT-PCR), and Western blot. Rescue experiments were performed to examine the effects of TAZ transfection and cell coculture. In the identified hUCMSCs (positive expressions of CD29, CD44, CD146, and CD105), overexpressed TAZ (pc-TAZ) enhanced the promotive effect of CGF membrane on cell viability, cell cycle, mineralization, ALP content and expressions of OPN, TAZ and osteogenic differentiation-related genes, and nuclear transfer. However, silencing TAZ showed opposite effects. The coculture of hUCMSCs and HPLFs further promoted the basic biological functions of HPLFs by upregulating osteogenic differentiation-related genes and COL-1 but downregulated MMP1 expression. Pc-TAZ could enhance the effect of CGF membrane on promoting periodontal tissue regeneration. CGF membrane promoted periodontal tissue regeneration through upregulating TAZ and osteogenic differentiation-related genes.